Alcohol Medications Development: Advantages and Caveats of Government/Academia Collaborating with the Pharmaceutical Industry. (1st April 2014) - Litten, Raye Z.; Ryan, Megan; Falk, Daniel; Fertig, Joanne
<x xml:space="preserve">Abstract</x> The process of developing pharmacological treatments for alcohol use disorder is notoriously complex and challenging. The path to market is long, costly, and inefficient. One way of expediting and reducing the drug development process is through collaborations—building partnerships among government, academia, pharmaceutical and biotechnology companies, healthcare organizations and advocacy groups, and the patients (end consumers) themselves. By forging collaborations, particularly with pharmaceutical companies, the alcohol treatment field stands to reap benefits in generating new medications for use in mainstream treatment settings. At the same time, there are certain caveats that should be considered, particularly by academic researchers, before entering into such partnerships. This commentary examines the advantages and caveats of government and academia collaborations with pharmaceutical companies.